Procollagen C-proteinase Enhancer 1 (PCPE-1) Functions as an Anti-angiogenic Factor and Enhances Epithelial Recovery in Injured Cornea - Massoudi, Dawiyat (Cell Tissue Res, 2017)
Procollagen C-proteinase enhancer 1 (PCPE-1) has been characterized as a protein capable of enhancing the activity of bone morphogenetic protein 1/tolloid-like proteinases (BTPs) in the biosynthetic processing of C-propeptides from procollagens I–III. This processing step is thought necessary to the formation of collagen I–III monomers capable of forming fibrils. Thus, PCPE-1 is predicted to play an important role in scarring, as scar tissue is predominantly composed of fibrillar collagen. Corneal scarring is of great clinical importance, as it leads to loss of visual acuity and, in severe cases, blindness. Here, we have investigated a possible role for PCPE-1 in corneal scarring. Although differences in corneal opacity associated with scarring following injury of Pcolce(−/−) and WT mice using full-thickness excision or alkali burn models of corneal injury were not grossly apparent, differences in procollagen I processing levels between Pcolce(−/−) and WT primary corneal keratocytes were consistent with a role for PCPE-1 in corneal collagen deposition. An unexpected finding was that neoangiogenesis, which follows alkali burn cornea injury, was strikingly increased in Pcolce(−/−) cornea, compared to WT. A series of aortic ring assays confirmed the anti-angiogenic effects of PCPE-1. Another unexpected finding was of abnormalities of epithelial basement membrane and of re-epithelialization following Pcolce(−/−) corneal injury. Thus, PCPE-1 appears to be of importance as an anti-angiogenic factor and in re-epithelialization following injury in cornea, and perhaps in other tissues as well.